ChemInform Abstract: Topochemical Synthesis of Alkali‐Metal Hydroxide Layers within Double‐ and Triple‐Layered Perovskites. Issue 16 (22nd April 2014) - Montasserasadi, Dariush; Mohanty, Debasish; Huq, Ashfia; Heroux, Luke; Payzant, Edward Andrew; Wiley, John B.
Abstract Alkali metal hydroxide layers within lamellar perovskites are formed by a two‐step topochemical synthesis.